Technique for Production of Holographic Diffraction Gratings Based on Inorganic Vacuum Photoresists - Danko, V.A.; Indutnyi, I.Z.; Lykanyuk, M.V.; Minko, V.I.; Shepeliavyi, P.E. (Science and Innovation, 2024)
An innovative project has been implemented to develop a technique for manufacturing the holographic diffraction gratings, which allows the engineers to produce high-quality diffractive elements with spatial frequencies from 600 to 3600 mm–1 for spectral devices. The guidelines for the implementation of this method have been elaborated and the pilot samples have been produced. The characteristics of pilot samples of holographic diffraction gratings manufactured under this project have been established to meet the specifications and the government standard 3-6128-86.